Academic Supervision Strategy Based On Prophetic Values: Innovation Of Improving Teacher Professionalism - Yuli Umro'atin; Prim Masrokan Mutohar; Ahmad Tanzeh; Akhyak (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to discover and develop a new theory of academic supervision techniques and approach based on prophetic value in improving teacher professionalism at MA Darul Huda Mayak Tonatan Ponorogo and MA Al-Mawaddah Coper Jetis Ponorogo. This study used a qualitative research multisite case study design. Data was obtained through in-depth interviews, participant observation, and document studies. This study in two Islamic Senior Hight Schools (MA Darul Huda and MA Al-Mawaddah). Results: Individual techniques, characterized by trustworthiness, discipline, openness, and responsibility, include: classroom visits, class observations, and individual meetings, group techniques are carried out with good communication, respect for privacy, and mutual motivation, include: teacher working group meetings, subject teacher deliberation meetings, training, and problem-solving groups. Academic Supervision Approach Based on Prophetic Values are Spiritual Approach, Supervisor provides guidance through religious activities, such as mujāhadah, dzikrul ghafilin, listening the Qur’an, and worship in months of Rajab and Ramadhan. Exemplary Approach is sets a good example for teachers, always quotes verses from the Qur'an during guidance, encourages teachers to always quote Qur'anic, and instills honesty. Administrative Approach with Prophetic Value, that Supervisor team check teachers' learning administration, with ta’hil maddah activity involving correcting learning materials, especially for new teachers, and reviewing preparations for oral exams in Arabic. Humanistic Problem-Solving Approach, that supervisor gives teachers the opportunity to discuss their problems in teaching and provides the best solutions by prioritizing openness and mutual respect. The study contributes a model of prophetic-based academic supervision integrating Islamic spiritual values with modern supervision techniques.